As concepções de linguagem no discurso do professor alfabetizador nas Séries Iniciais do Ensino Fundamental I - Almeida, Tatiana Vieira (2020)
The issue of literacy is not a recent issue in our literature. However, there still does not seem to be a consensus on what this activity is and their importance in learning a language, in this case, Portuguese. The reason for this, perhaps, is in the way the teacher conceives the language and how it affects their practice, consequently, reaching the student. Authors such as Travaglia (1998) and Geraldi (1998), in addition to Braggio (1992) and Ferreiro (1988), have concepts of language that we use to address the theme of this research. Given this context, the present study aimed to outline a profile of the training of teachers who are in classrooms considered to be literacy educators, in two schools in the city of Fortaleza, in order to understand the notion of language that these teachers bring to their practices. To achieve this objective, a theoretical overview was first drawn up on some conceptions of language and literacy, which guided the analysis of the corpus. The latter, in turn, was formed by interviews with six teachers, two from each series of the literacy cycle, from the 1 st, 2 nd and 3 rd grades, in addition to the sample of some activities used in the classroom with the objective of teaching reading and writing. Through the analysis of these data, it was possible, based on the theoretical overview and official documents of education in the country, to build a probable profile of literacy teachers.